The key factors of the industrial revolution 4.0 in the Malaysian smart manufacturing context - Abdul Hamid, Mohd Syaiful Rizal; Masrom, Nor Ratna; Mazlan, Nur Athirah (IGI Global, 2022)
IR 4.0 is a new phase for the current trend of automation and data exchange in the manufacturing industry that focuses on cloud computing, interconnectivity, the internet of things, machine learning, cyber physical learning, and creating smart factories. The purpose of this article was to unveil the key factors of the IR 4.0 in the Malaysian smart manufacturing context. Two key data collection methods were used: (1) primary data from the face-to-face interview and (2) secondary data from the previous study. Significantly, five key factors of IR 4.0 were considered for this study: autonomous production lines, smart manufacturing practices, data challenge, process flexibility, and security. As a result, IR 4.0 for quality management practices might get high impact for the best performance assessment, which is addressed in various ways. Few studies in this area have been conducted in the Malaysian manufacturing sector to recommend the best practices implemented from the managers’ perspectives. For scholars, this enhances their understanding and highlights opportunities for further research.